Penerapan Metode Algoritma C4.5 Untuk Prediksi Mahaiswa Non Aktif - Irmayansyah Irmayansyah; Erisya Lastrini (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
The problem of non-active students is something to be aware of because it can affect the quality of education and result in a decrease in campus financial income. If the problem of inactive students can be predicted faster, then the management can prevent and anticipate early. To solve the problem, c4.5 algorithm is applied to the prediction of non-active students in order to produce patterns based on classification results. By using IPS, Attendance, Annual Income, cost sources, and payment status. This is done to monitor students who are potentially non- active so as to anticipating for the decline of active students. In this study, feasibility test has been conducted, with a feasibility value of 87.50%, and also has been conducted accuracy test using confussion matrix formula with 81% accuracy result.